2011
DOI: 10.4000/ries.1073
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum, entre modèle rationnel et irrationalité des sociétés

Abstract: Revue internationale d'éducation de Sèvres | avril 2011Le curriculum dans les politiques éducatives Curriculum, entre modèle rationnel et irrationalité des sociétésCurricula: between rational model and irrational societies Currículum, entre modelo racional e irracionalidad de las sociedades

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
5
0
8
Order By: Relevance
“…Vi è infine un terzo livello, quello del curricolo trasposto (Joannert, 2011;Rossi, 2016) o del visible design, che prevede la costruzione di artefatti che visualizzino la macro e la micro-progettazione in classe in un formato grafico e linguistico adatto alla classe. Sono gli artefatti progettuali da condividere con gli studenti, come si vedrà successivamente, utili per l'orientamento e la coprogettazione con gli studenti.…”
Section: Premessaunclassified
“…Vi è infine un terzo livello, quello del curricolo trasposto (Joannert, 2011;Rossi, 2016) o del visible design, che prevede la costruzione di artefatti che visualizzino la macro e la micro-progettazione in classe in un formato grafico e linguistico adatto alla classe. Sono gli artefatti progettuali da condividere con gli studenti, come si vedrà successivamente, utili per l'orientamento e la coprogettazione con gli studenti.…”
Section: Premessaunclassified
“…In fact, it is quite dynamic. It covers the various curricular levels (D 'Hainaut 1981'Hainaut , 1988Jonnaert 2011a;Keeves 1992;Perrenoud 1984) and regularly changes form. The official texts prepared by ministries appear between the lines in the various documents used by teachers and take on a very specific form during teaching/ learning activities in the classroom, often remote from the curriculum prescribed in official texts.…”
Section: A Proposal For Conceptual Clarificationmentioning
confidence: 99%
“…Current curriculum research, as well as development research in the field, tends to show how relative the hierarchy is between these boxes, focusing on phases versus forms Table 2 Cross-referencing the phases of a curriculum with the different forms it can take C.e C.f (Jonnaert 2011a). The everyday reality in education systems and their curricula can often be quite far removed from the abundant current debates, theories, and research on curricula, such as that reported in the European Educational Research Journal, International Review of Educational Reform, Journal of Curriculum Studies, Learning and Instruction, and Prospects, Quarterly Review of Comparative Education.…”
Section: Cmentioning
confidence: 99%
See 2 more Smart Citations